Preventing Xenophobia in Africa: What Must the African Union Do? - Adeola, Romola (African Human Mobility Review, 2021)
The issue of xenophobia has, for many years, been one of the pressing challenges in Africa. While South Africa currently appears as a poster-child of this problem in Africa, the issue of xenophobia is not solely a South African problem. Traces of these attacks have long existed since the 1960s with countries such as Ghana and Nigeria raising agitations against each other and occasioning displacements of millions of people. Similar to the South African narrative, the agitations were borne out of a need to create an economic haven, the realisation of which was impeded by the influx of foreign populations. In recent years, the issue of xenophobia has equally resonated in the treatment of Somalis in Kenya following the attacks by the Somali-dominated insurgency group and in the treatment of Rwandan refugees in western districts of Uganda.